DETERMINANTS OF PROFITABILITY AMONG INDONESIAN LISTED FIRMS: THE ROLE OF LEVERAGE, EFFICIENCY, AND MARKET VALUATION - Yopi Saputra; Muhammad Fahmi; Vitriyan Espa; Rudy Kurniawan; Sari Rusmita (Asosiasi Dosen Muda Indonesia, 2025)
This study investigates the determinants of corporate profitability among publicly listed companies in Indonesia. Using firm-year data from the Indonesia Stock Exchange for the 2020–2024 period, we examine how capital structure, operational efficiency, market valuation, investor expectation, firm size, and liquidity relate to profitability. Profitability is proxied by Return on Assets (ROA) and Return on Equity (ROE). We estimate panel regressions and perform robustness checks using alternative specifications and multicollinearity diagnostics. The results show that operational efficiency (net profit margin) and market valuation (price-to-book) are positively and significantly associated with profitability, while leverage (debt-to-equity) exhibits a negative and economically meaningful effect. Investor expectation (price-to-earnings) is positively related to profitability, although the magnitude varies across model choices and profitability proxies. Firm size contributes positively, whereas excessive liquidity is linked to lower profitability, consistent with agency and idle-cash arguments. The findings highlight the importance of balancing growth signals with prudent capital structure and cost efficiency to enhance shareholder value. Policy implications are discussed for managers, investors, and regulators in emerging markets.